Sistem Monitoring Administrasi Penjualan Kendaraan Berbasis web Dengan Administrative Workflow System - Dewandaru, Kalista Wiwaha; Supriyanto, Antok; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
An Administration Document is necessary for sales vehicle and must be completed by customers. This Administrative document collection is done at the one of Astra isuzu branch because this process involving cooperation between customers, sales units, Sales leasing, An Administration document for vehicle sales also serves as one of the absolute requirement on leasing demand credit application chosen by the applicant vehicle loans and determine the vehicle's credit application is accepted or not. There is a problem that has occurred during this time, where there are no regulation about deadline for collection of Administrative document that make delays in the all process of ordering vehicles. With the implementation of the Administrative Workflow Systems in this Monitoring system can help the customer to accelerate the collection of administration documents of sales vechicle and help the sales unit to immediately process the customer booking request and help sales leasing to immediately process subcribers vehicle if the loan application is accepted or not.